Catalytic effect of Ca and K on CO2 gasification of spruce wood char. (15th June 2015) - Perander, M.; DeMartini, N.; Brink, A.; Kramb, J.; Karlström, O.; Hemming, J.; Moilanen, A.; Konttinen, J.; Hupa, M.
Highlights: Ca and K were loaded to an acid washed wood sample by ion-exchange. CO2 -gasification reactivity was studied using TGA at 850 °C. The reaction rate increased linearly with the content of Ca and K in the wood. A carbonate layer forming on the char slows the final gasification reaction. Abstract: Gasification is one route to produce chemicals and liquid fuels from biomass. The gasification of the char is catalyzed by alkali and alkaline earth metals in the biomass. In this work the catalytic effect of calcium (Ca) and potassium (K) on CO2 gasification of spruce wood was studied using a thermo gravimetric analyzer (TGA). The ash-forming elements were first removed from the wood using an acid leaching method. Then, various concentrations of K and Ca were absorbed to the wood by ion-exchange to carboxylic and phenolic groups, impregnation of K2 CO3 or physically mixing of CaC2 O4 . The prepared spruce samples were placed in a mesh holder and gasified in the TGA at 850 °C in 100% CO2 . The results demonstrate that the gasification rate of the char increased linearly with an increase in the concentration of Ca or K. Crystalline CaC2 O4 distributed only at the surface of the wood particles resulted in low catalytic activity. The catalytic activity of Ca was higher than K in the beginning of char gasification but the catalytic effect of Ca decreased earlier than the catalytic effect of potassium. Further, the char structure was investigated by SEM–EDX. The SEM analysis from interrupted gasification experiments showed the formation of CaCO3 and K2 CO3 layer on the char surface. By adding corresponding levels of Ca and K as the original spruce to the acid washed sample, a similar gasification reactivity was obtained at 850 °C.